2015
DOI: 10.2174/1389203716666150213161311
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Enzymes and their Receptors in Invertebrates: An Evolutionary Perspective

Abstract: Lysosomal biogenesis is an important process in eukaryotic cells to maintain cellular homeostasis. The key components that are involved in the biogenesis such as the lysosomal enzymes, their modifications and the mannose 6-phosphate receptors have been well studied and their evolutionary conservation across mammalian and non-mammalian vertebrates is clearly established. Invertebrate lysosomal biogenesis pathway on the other hand is not well studied. Although, details on mannose 6-phosphate receptors and enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Both of these GO categories were dominated by glycoside hydrolases, sulfatases, proteinases and components of the proteasome, previously reported as lysosomal enzymes17 (Table 1). …”
Section: Resultsmentioning
confidence: 81%
“…Both of these GO categories were dominated by glycoside hydrolases, sulfatases, proteinases and components of the proteasome, previously reported as lysosomal enzymes17 (Table 1). …”
Section: Resultsmentioning
confidence: 81%
“…vannamei [ 53 , 54 ]. It was reported that mannose-6-phosphate receptor involved in the immunological function in invertebrates [ 55 ]. Integrins are a family of adhesion receptors which regulate cell proliferation, differentiation, leukocyte migration, and complement receptor-dependent phagocytosis, and integrins β play an important role for the balanced activation of immune defense responses especially during the encounter of infections in L .…”
Section: Discussionmentioning
confidence: 99%
“…The co-localization of both CIMPR and cathepsin D indicated that internalization and lysosomal transport was mediated by the receptor. In addition to the mannose 6-phoshate receptors, sortilin may play a role in lysosomal transport of this enzyme which needs to be validated with additional experiments [4,7]. However, previous reports of both the mannose 6-phosphate receptors in invertebrates such as echinoderms and mollusks indicates the lysosomal biogenesis in these organisms follows mannose 6-phosphate dependent pathways which is found to be evolutionarily conserved in higher vertebrates including mammals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways act in synergy and one often complements in the absence of the other for the efficient lysosomal transport of cathepsin D. Both the receptors have been identified in mammals and putative homologs of the receptors responsible for the transport of lysosomal enzymes have been identified in echinoderms and mollusks [12]. Recent studies have reported the properties of lysosomal enzymes and their possible receptor-mediated lysosomal transport in invertebrates [7]. As the starfish cathepsin D has been affinity purified and preliminarily characterized [10], the present study was undertaken to gain new insights into two important properties of the enzyme (i) comparing its proteolytic activity against mammalian proteins and (ii) to study the MPR mediated lysosomal localization of the purified enzyme in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%